A three-electrode multi-module sensor for accurate bodily-kinesthetic monitoring - Wang, Haobin; Yu Song; Guo, Hang; Ji Wan; Miao, Liming; Xu, Chen; Zhongyang Ren; Chen, Xuexian; Zhang, Haixia (Nano Energy, 2019)
In response to the ongoing challenges for health care and human motion monitoring, this work proposes a three-electrode multi-module sensor (TEMS) integrating proximity feedback, compression sensing and stretching perception. With the assist of the porous carbon nanotubes (CNTs)-polydimethylsiloxane (PDMS) patch in optimized parameters, the unification of the device's out-of-plane non-contact sensing and in-plane contact segmental detection is realized. Besides, coordinated with a set of symmetrically patterned Ag nanowires (NWs) electrodes with specified initial conductivity, the device is highly-sensitive to two-dimensional strains and qualified for recognizing the horizontal tension strain as small as 0.077% and the vertical pressure exerted by a piece of scrip (0.18 Pa) in fast response (millisecond level). The anti-interference ability of the signals is ensured by the PDMS encapsulation and regional stiffness of the device. Furthermore, the simplified fabrication process based on PDMS doping/modification is suitable for human skin-attachable applications, especially as the accurate differentiation of similar motions and the time-phased judgment of continuous movements through collaboration among acquisition results.
Keywords: Motion-monitoring; Multi-module; Three-electrode-sensing